Click-Chemistry-Assisted Alteration of Glycosaminoglycans for Biological Applications - Smritilekha Bera; Dhananjoy Mondal (SynOpen, 2023)
This short review describes the assistance of click chemistry in the chemical modification of glycosaminoglycans. Through an alkyne-azide 1,3-dipolar cycloaddition reaction, the chemically and physiologically stable triazole unit connects glycosaminoglycans with other labelled or attached functionalities. The synthesized glycosaminoglycan (GAG) conjugates act as drug carriers, forming hydrogels or nanohydrogels for localized drug delivery or injectable GAGs and so on. These are used in research on antithrombotic agents, protein binding, and hepatocyte growth factors, as well as in mechanistic studies of glycosaminoglycans biosynthesis and wound healing. 1 Introduction 2 Synthetic Modification of GAGS 3 Click Chemistry 4 Modification of GAGS Applying Click Chemistry 5 Conclusions 6 Abbreviations